PENERIMAAN DIRI DAN DUKUNGAN SOSIAL HUBUNGANNYA DENGAN PENYESUAIAN DIRI WANITA YANG MENGHADAPI MASA MENOPAUSE: PENERIMAAN DIRI DAN DUKUNGAN SOSIAL HUBUNGANNYA DENGAN PENYESUAIAN DIRI WANITA YANG MENGHADAPI MASA MENOPAUSE - Chaerani, Rachma Fajri; Rahayu, Anizar (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2018)
Abstract Menopause is a sure time for every woman in middle age. The arrival of the menopause is accompanied by changes in the decline in physical condition. This often causes anxiety for every woman, especially those who are not ready to deal with it. This study aims to determine selfacceptance and social support in relation to the adjustment of women who face menopause. This study uses a quantitative approach, the population is women in RW 03 Bintara VIII, kelurahan Bintara Bekasi Barat aged 47 - 52 years. A total of 152 people were taken using simple random sampling technique. Methods of data collection using a Likert model scale consisting of self-adjustment scale adapted from the theory of Desmita (2016), self-acceptance scale compiled from the Supratiknya theory (1995) and the scale of social support referred to by the theory of Sarafino and Smith (2012). Data analysis technique uses Pearson Product Moment correlation in SPSS 24.0 for Windows program. The results of the analysis using regression obtained R value of 0.354 which means there is a significant positive relationship of self-acceptance and social support with self-adjustment. From the Stepwise test found the contribution of self-acceptance and social support variables to adjustment is 12.5%. The contribution of self-acceptance is greater than social support.